PEMBUATAN WEBSITE INVENTARIS BARANG DI KOBER AULIA - Muhammad, Thomas Lazuardi; Darsiti, Darsiti (JURNAL ILMIAH INFORMATIKA, 2025)
The Goods Inventory Website is a website-based application used to manage and track stock of goods or assets in an agency in Kober Aulia, an important means to provide convenience for teachers to record goods in Kober Aulia. Managing goods data is often a challenge for Kober.Kober today, which still uses the manual method of recording one by one through books. This study aims to design a website-based application that can do bookkeeping or recording of goods neatly and make it easy to see stock or new goods to be submitted to the center for reporting learning facilities and infrastructure. To overcome this problem, it can be overcome by CMS (Content Management System). CMS is a system that can change data content dynamically. This inventory website is made using Laravel which is easy to use and also uses Visual Studio Code as a supporting application and uses MySQL as a database to store data. This application will certainly be very easy to use by users with clear information and is not difficult to operate. This application is adjusted to the needs of users who currently still find it difficult to record goods in Kober Aulia and still use manual books to record existing stock of goods.